Gestão de recursos hídricos e ação coletiva: uma análise da efetivação da cobrança pelo uso da água. - Ivania Moraes Soares (2009)
This research analyses the water use charge, one of the water resources management instruments established by the Federal Law 9.433/97 also known as Water Law. The study was developed from the pertinent theoretical outline, as well as the study of National and State Water Resources Policies. The assumptions assumed in this work are: first, the actors act rationally with the aim of maximizing their preferences; and, second, the public good provision only occurs via cooperation. The hydrographic basin committees have been used as objects of analysis, established by the cited federal law as management organs of waterresources within the ambit of the water basin. Three committees have been chosen given the stage of the debate in relation to the charge effectiveness in each one of them, namely: 1)Comitê da Bacia Hidrográfica do Rio das Velhas; 2) Comitê da Bacia Hidrográfica do RioParaopeba; and 3) Comitê da Bacia Hidrográfica do Rio Paraíba do Sul. Interviews have been made with committees´ members to analyze the interaction patterns of these actors, aiming to answer to the question: Why the instrument of charge management for the use of water,predicted in the Water Law, has not been accomplished equally in the three committees mentioned in this work, despite the fact that all of the basins are under the same legal prevision of charge? Thus, one sought to verify if the committees´ actors use some dilatory expedients of charge for the use of water.